2015
DOI: 10.1002/jcph.561
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of disease‐mediated therapeutic protein–drug interactions between an anti–interleukin‐6 monoclonal antibody (sirukumab) and cytochrome P450 activities in a phase 1 study in patients with rheumatoid arthritis using a cocktail approach

Abstract: This therapeutic protein-drug interaction study evaluated the disease-mediated effect of sirukumab (anti-interleukin 6 [anti-IL-6] monoclonal antibody) on the pharmacokinetics of the cytochrome P450 (CYP) probe substrates midazolam (CYP3A), omeprazole (CYP2C19), warfarin (CYP2C9), and caffeine (CYP1A2) in patients with active rheumatoid arthritis (RA). Twelve patients with C-reactive protein (CRP) ≥ 8.0 mg/L at screening received oral administration of a CYP probe cocktail consisting of 0.03 mg/kg midazolam, 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
93
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 72 publications
(100 citation statements)
references
References 19 publications
7
93
0
Order By: Relevance
“…The reported baseline systemic IL-6 concentrations were highly varied, ranging from 1.24-11 pg/mL in healthy subjects (16,17,(20)(21)(22)(23)(24)(25)(26) and from 3.51-119 pg/mL in RA patients (8,10,(14)(15)(16)(17)(18)(19)(20). Based on the pooled analysis using data available in the literature, the estimated average systemic IL-6 concentrations in healthy subjects was 3.27 ± 2.38 pg/mL (Fig.…”
Section: Pooled Analyses Of Systemic Il-6 In Ra Patients and In Healtmentioning
confidence: 99%
See 4 more Smart Citations
“…The reported baseline systemic IL-6 concentrations were highly varied, ranging from 1.24-11 pg/mL in healthy subjects (16,17,(20)(21)(22)(23)(24)(25)(26) and from 3.51-119 pg/mL in RA patients (8,10,(14)(15)(16)(17)(18)(19)(20). Based on the pooled analysis using data available in the literature, the estimated average systemic IL-6 concentrations in healthy subjects was 3.27 ± 2.38 pg/mL (Fig.…”
Section: Pooled Analyses Of Systemic Il-6 In Ra Patients and In Healtmentioning
confidence: 99%
“…Consistently, a recent in vivo drug-drug interaction (DDI) study conducted in RA patients showed that the administration of an anti-IL-6 receptor monoclonal antibody (mAb) tocilizumab reversed IL-6-induced suppression of CYP3A4 and CYP2C19 activity, as reflected by a significant decrease in systemic exposure to simvastatin (a CYP3A4 substrate) and omeprazole (a CYP2C19 substrate) following tocilizumab treatment (8,9). Another cocktail clinical DDI study conducted in RA patients also reported that treatment with an anti-IL-6 antibody sirukumab led to decreases in systemic exposure to CYP3A4 substrate midazolam, CYP2C19 substrate omeprazole, and CYP2C9 substrate S-warfarin but increases in systemic exposure to CYP1A2 substrate caffeine (10), further confirming the possibility of therapeutic protein-drug interactions (TP-DI) between anti-IL-6 therapeutic proteins (TPs) and smallmolecule drugs in RA patients via modulation of CYP enzymes.…”
Section: Introductionmentioning
confidence: 95%
See 3 more Smart Citations